Bioactive compounds and physicochemical characterization of dried apricot (Prunus armeniaca L.) as affected by different drying temperatures. Issue 1 (1st January 2019) - Vega-Gálvez, Antonio; Quispe-Fuentes, Issis; Uribe, Elsa; Martinez-Monzo, Javier; Pasten, Alexis; Lemus-Mondaca, Roberto
ABSTRACT: The influence of diverse hot-air drying temperature on bioactive compounds, nutritional components, and physical aspects of apricot ( Prunus armeniaca L. var. Tilton) fruits from 40°C to 80°C was evaluated. Firstly, drying kinetics was modeled by Diffusion model and Weibull equation, this last provided a good fit to the experimental data. The effect of drying conditions on the color and microstructure showed noticeable modifications due to an increase of air-drying temperature. Besides, a reduction of antioxidant activity, total phenolic and flavonoid contents with an increase of drying temperature were observed. As to vitamin C and β-carotene were much more affected by the long drying times (>1000 min) than high temperatures (>60°C). Sucrose, fructose, and glucose were identified in all apricot samples, being sucrose the predominant sugar. Thus, results from the present study indicate that the hot-air drying technology continues to be applicable for obtaining a dried functional product of good quality.